The effectiveness of Adler's parenting education program on school bonding and adolescent high-risk behaviors - Ebrahimtabar Gerdroodbari , Esfandiar; Emadian , Seyedeh Olia; Mirzaian , Bahram (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to determine the effectiveness of Adler's parenting education program on school bonding and high-risk behaviors of adolescents. Methods: The present research method was quasi-experimental with pre-test, post-test design and follow-up with a control group. The statistical population of this research is. The statistical population of the study is 665 mothers of all female high school students in East Bandapi, Babol, who are studying in the academic year of 2009-2010, of which 60 are students with high-risk behavioral problems and their mothers The input criteria of the study were consistent with purposive non-random sampling method and were randomly divided into two groups of 15 experimental and control. The experimental group received a parenting training program based on the Bruegel training package (2016) in 8 sessions of 120 minutes per week. Before and after the intervention, the school connection questionnaire (Rezaei Sharif, 2012) and the high-risk behaviors questionnaire (Zad Mohammadi et al., 1390) was performed in both groups. Data were analyzed by repeated measures analysis of variance using SPSS-22 software. Results: The results of this study showed that the Adler parenting program training program increased parental care bond (F = 5.53, P